PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI AKUNTANSI PENERIMAAN DAN PENGELUARAN KAS MENGGUNAKAN VISUAL STUDIO 2013 DAN MYSQL PADA CV. PASIPA JAYA - Tresnawati, Shandy; Fauzi, Findri (Journal of Economics, Accounting, Tax, and Management (JECATAMA), 2023)
This study aims to analyze, design, implement and test the accounting information system for cash receipts and expenditures using visual studio 2013 and MySQL. The method used is a qualitative research method with System Development Life Cycle (SDLC). Data collection techniques in this study used observation techniques, interviews, and literature studies. The analysis is carried out using the PIECES method. Design and implementation of accounting information system for cash receipts and expenditures using Visual Studio 2013 and MySQL and information reports with Crystal Report. System testing is carried out with a User Acceptance Test (UAT) with black-box testing techniques. This system can make it easier to enter data, make financial reports or other needs, and can maintain the integrity and accuracy of data.